JUDI ONLINE SEBAGAI PROBLEMATIKA YANG MENGGEROGOTI DIMENSI KEHIDUPAN BERSARANG DIBALIK KEMAJUAN TEKNOLKOGI DIGITAL - Izra Fauzi; Suaidi Suaidi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Gambling is an act that is prohibited by religion, because it will cause losses that have a negative impact on human life, both in terms of the economy and social life. The consequences of gambling affect the development and intelligence of the mind, and will even lead to criminal acts related to the economy such as theft and even murder. The consequences of gambling lead to complex and problematic problems with significant social, economic and legal impacts. Although various efforts have been made to eradicate it, technological developments continue to present new challenges. The future of online gambling can be seen through several scenarios that require serious attention and strategic steps. Meanwhile, dependence on gambling can lead to serious addiction, which has a negative impact on the social, economic and mental health of individuals and their families.